Raising Bilingual Awareness Utilizing Montessori Philosophy and Multi-modal Learning - Debora Chaterin Simanjuntak; Agustinar Centhya Sinaga (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
Access to engaging and developmentally appropriate English instruction for young learners in Indonesia remains uneven, and parents’ understanding of bilingualism is not always aligned with current research. This study investigated how a Montessori-inspired, multi-modal English learning program supported young children’s engagement and emerging bilingual awareness, and how parents perceived its impact. This study was conducted over two semesters in Parongpong and involved a lecturer, a certified Montessori teacher, and 14 pre-service teachers who facilitated learning sessions. Data were collected from approximately 30 young learners per program cycle, with 15 children and several parents purposively selected for semi-structured interviews. Data were analyzed using deductive thematic analysis based on categories from the literature on bilingualism, multi-modal learning, and parental involvement. The findings show (1) multi-modal, hands-on activities grounded in Montessori principles increased learners’ enthusiasm and supported vocabulary retention; (2) a gap remained between receptive and productive skills, especially when learners were asked to speak in front of peers; (3) both children and parents held positive attitudes toward bilingualism and linked English to future opportunities; and (4) parents hoped for clearer guidance to continue bilingual support at home. The study suggests that Montessori-based, multi-modal instruction can be a viable model for early bilingual education in community settings, provided that explicit oral-language scaffolds and home–school collaboration are strengthened.